ANALISIS FAKTOR PRIBADI DAN PSIKOLOGIS TERHADAP KEPUTUSAN PEMBELIAN PRODUK KOPI BUBUK CAP OBOR DI KOTA PONTIANAK - Jamaluddin, Jamaluddin; Dolorosa, Eva; Imelda, Imelda (Fakultas Pertanian Universitas Tanjungpura, 2019)
The increasing of enthusiast drink coffee on the community has led to the company interest in splitting coffee products business. The presence of the companies in crushing coffee of course will give the effect on local coffee companies that is generally still small scale and have low competitiveness. One of Pontianak coffee products is a